Lactobacillus gasseri Causing Bilateral Empyema - Angela Esquibel; Ala S. Dababneh; Bharath Raj Palraj (Case Reports in Infectious Diseases)
Lactobacilli are common commensal bacteria found in the gastrointestinal and genitourinary tract. Although they are usually thought to be nonpathogenic, there have been several cases that demonstrate severe infections caused by these microorganisms. This is a case of a 49-year-old male with previously undiagnosed type two diabetes mellitus who presented with a 3-month history of cough and was found to have right sided Lactobacillus gasseri empyema for which he underwent video-assisted thoracoscopic surgery (VATS) with chest tube placement. He subsequently developed a left sided pleural empyema for which the aspiration also grew out L. gasseri. The patient made a complete recovery and was seen for four months in follow-up after his initial presentation.